2018
DOI: 10.1146/annurev-psych-122216-011725
|View full text |Cite
|
Sign up to set email alerts
|

Improving Student Outcomes in Higher Education: The Science of Targeted Intervention

Abstract: Many theoretically based interventions have been developed over the past two decades to improve educational outcomes in higher education. Based in social-psychological and motivation theories, well-crafted interventions have proven remarkably effective because they target specific educational problems and the processes that underlie them. In this review, we evaluate the current state of the literature on targeted interventions in higher education with an eye to emerging theoretical and conceptual questions abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
243
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(254 citation statements)
references
References 71 publications
7
243
0
4
Order By: Relevance
“…This indicates that students from low ESCS backgrounds may benefit from increased motivational support in science. Indeed, Harackiewicz, Canning, Tibbetts, Priniski, and Hyde () (see also Harackiewicz & Priniski, ) have shown that the motivation and achievement of students from low ESCS backgrounds improved with targeted motivation interventions in science. Science teachers may consider providing similar motivational support and structure to these students in their classrooms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that students from low ESCS backgrounds may benefit from increased motivational support in science. Indeed, Harackiewicz, Canning, Tibbetts, Priniski, and Hyde () (see also Harackiewicz & Priniski, ) have shown that the motivation and achievement of students from low ESCS backgrounds improved with targeted motivation interventions in science. Science teachers may consider providing similar motivational support and structure to these students in their classrooms.…”
Section: Discussionmentioning
confidence: 99%
“…To improve students' interest in and enjoyment of science, teachers may consider illustrating the usefulness and relevance of science to students' lives. Teachers can do this by (a) directly communicating this to students, or (b) providing students with tasks that have them explore and identify the personal relevance of science (Harackiewicz & Priniski, ). Although a combination of these strategies is suggested (Canning & Harackiewicz, ), the latter strategy has been found to be the most effective for all ability levels (Hulleman, Godes, Hendricks, & Harackiewicz, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, should semester-long change patterns in science identity be differentially related to grades in a course and/or pursuit of science majors the following semester, it would pinpoint science identity as a valuable construct to support in promoting higher achievement and retention in science for students in the course. Existing intervention approaches from an expectancy-value perspective have focused primarily on utility value (e.g., Harackiewicz & Priniski, 2017) and have not yet explored supports for identity-based forms of value. Some experimental evidence suggests that identity-related beliefs can be supported in middle school through messages about the congruence of personal and aspirational future identities (Destin & Oyserman, 2010; Elmore & Oyserman, 2012), and correlational studies have focused on potential supports for science identity in college via extracurricular involvement in science enrichment experiences and/or mentoring (Chemers et al, 2011; Hernandez et al, 2018).…”
Section: Outcomes Related To Science Identity Trajectoriesmentioning
confidence: 99%
“…Academic interventions are strategically constructed to educate student participants on skill building and promote skill fluency, or to motivate the application of existing skills in new circumstances and settings [23]. According to Harackiewicz and Priniski [24], the sphere of higher education has experienced an increase of academic interventions developed to improve academic outcomes in student performance. Researchers have proposed academic interventions and implemented programs for STEM students with hopes of finding multiple solutions to the low persistence rates within STEM majors and careers [25].…”
Section: Academic Interventions In Stemmentioning
confidence: 99%